Bibliometric Analysis of Postgraduate Theses on Exercise Addiction in Türkiye - Sönmez Ünüvar, Bayram; Keskin, Tahir; Ergan, Mesut; Başkurt, Ferdi (Addicta: The Turkish Journal on Addictions, 2025)
The aim of this study is to delineate the common characteristics and research trends of postgraduate theses related to exercise addiction in Türkiye, thereby providing a guiding resource for researchers and practitioners in this field. In this bibliometric analysis, a total of 86 theses were obtained from the Council of Higher Education Thesis Center using the search term exercise addiction.” Out of these theses, 84 met the inclusion criteria, providing a comprehensive overview. The majority of these theses were written in Turkish (92.85%), with an average page count of 91.01 pages. The subjects of the theses varied widely, with sports being the most prevalent area of focus (76.19%). Health sciences institutes were the primary contributors to research in this area (44.04%), emphasizing the multidisciplinary nature of the topic. The Exercise Addiction Scale- 17 emerged as the most commonly used scale (58.33%), indicating a standardized approach to assessing addiction levels. Participant profiles ranged from regular exercisers to diagnosed patients, highlighting the diverse scope of research. Furthermore, the distribution of theses by publication year showed an increasing trend, with 2022 being the most active year. This comprehensive analysis provides valuable insights for researchers and practitioners, guiding future studies and interventions in this important area of study.